PEMBELAJARAN BERDASARKAN TEORI VAN HIELE BERBANTUAN HANDS ON ACTIVITY (HOA) UNTUK MENINGKATKAN KOMPETENSI PENGETAHUAN DAN KETERAMPILAN PEMECAHAN MASALAH - Ratna Titi Wulandari; Akbar Sutawidjaja; Susiswo Susiswo (Graduate School of Universitas Negeri Malang, 2016)
This study aims at examining the learning based on Van Hiele’s theory with Hands-on Activity (HOA) assisted to improve students’ knowledge and skill. The learning based on Van Hiele’s theory with Hands-on Activity (HOA) assisted consists of zero level, first level, and second level. In each level, there are five stages they are Information, guide orientation, explicitation, free orientation, integration in which Hands-on Activity (HOA) is used in one of the stages. This research is a classroom action research focusing on VII E in SMPN 3 Grabag, Magelang Regency. The result of this study showed that the learning based on Van Hiele’s theory with Hands-on Activity (HOA) assisted improves the students’ knowledge and skill.Penelitian ini bertujuan mendeskripsikan pembelajaran berdasarkan teori van Hiele berbantuan HOA untuk meningkatkan kompetensi pengetahuan dan keterampilan siswa. Pembelajaran berdasarkan teori van Hiele berbantuan HOA, yaitu pembelajaran yang melalui level 0, level 1, dan level 2. Setiap level ada 5 tahap: information, guide orientation, explicitation, free orientation, integration dan HOA digunakan di salah satu tahap tersebut. Penelitian ini adalah Penelitian Tindakan Kelas VII E di SMP N 3 Grabag, Kabupaten Magelang. Setelah peneliti melakukan pembelajaran berdasarkan teori van Hiele berbantuan HOA ternyata pengetahuan dan keterampilan pemecahan masalah garis dan sudut siswa tersebut meningkat.